Inclusive Education as a Tool of Promoting Quality in Education: Teachers' Perception of the Educational Inclusion of Students with Disabilities - Fátima Rosado-Castellano; Susana Sánchez-Herrera; Lucía Pérez-Vera; María Jesús Fernández-Sánchez (MDPI AG, 2022)
Teachers' attitudes towards inclusion are influenced by factors such as training and teaching experiences. However, there is no conclusive trend correlating specific factors with negative or positive attitudes. The aim of this study is to understand the reality of inclusion in schools in Extremadura, Spain, from the teachers' point of view. To do so, a reliable and valid questionnaire was administered to a total of 106 teachers from more than 20 schools in Extremadura, followed by the subsequent categorization of more than 300 comments obtained from semi-structured interviews with 16 teachers. The results show that teachers value an inclusive philosophy in schools, especially in terms of values and policies. Teachers working in special schools had a moderately more positive perception of the degree of inclusion in their school, although there were hardly any significant differences compared to teachers in other types of schools, nor were there any significant differences according to teachers' prior training. Finally, the importance of evaluation in the creation of plans to guarantee an improvement in the attention to diversity is assessed.